2002
DOI: 10.1080/000164802753648196
|View full text |Cite
|
Sign up to set email alerts
|

Modified Method of Acoustic Rhinometry

Abstract: Acoustic rhinometry is a well-known method for evaluating nasal cavity patency using sound waves. The method produces graphical information on cross-sectional areas, the distances between these areas and the nostril and the nasal volume. We used this method to evaluate 40 children aged between 7 and 13 years old with complaints of nasal obstruction. All patients underwent endoscopic examination of the nasal cavity, and only children presenting with hypertrophic inferior nasal turbinates and with no history or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 9 publications
2
8
0
6
Order By: Relevance
“…In other studies, specific nasal cavity cross-sectional areas (besides the MCA) were shown to correlate with specific anatomic landmarks on NE, 16,31 which may be clinically significant in certain subpopulations that were not studied here. Notably, we did not account for patient age and size in our assessment of the AR variables.…”
Section: Discussionmentioning
confidence: 89%
“…In other studies, specific nasal cavity cross-sectional areas (besides the MCA) were shown to correlate with specific anatomic landmarks on NE, 16,31 which may be clinically significant in certain subpopulations that were not studied here. Notably, we did not account for patient age and size in our assessment of the AR variables.…”
Section: Discussionmentioning
confidence: 89%
“…Sua introdução na prática clínica, como método de avaliação da geometria nasal, se deu com o trabalho de Hilberg et al (1989 Grymer et al (1989Grymer et al ( , 1991Grymer et al ( , 1997, Hilberg et al (1990), Lenders e Pirsig (1990), Lenders et al (1991), Kesavanathan et al (1995), Morgan et al (1995), Roithmann et al ( , 1997, Millqvist e Bende (1998), Corey et al (1998), Tomkinson e Eccles (1998), Silkoff et al (1999), Kunkel et al (1999), Sung et al (2000), Larsson et al (2001) A técnica tem também sido empregada por vários autores para estimar a obstrução de vias aéreas nasais de diferentes etiologias. Nessas condições, valores subnormais foram observados por autores como Grymer et al (1989), Hilberg et al (1990), Lenders e Pirsig (1990), Lenders et al (1991), Fisher et al (1995), Roithmann et al ( , 1997, Gilain et al (1997), Kunkel et al (1997), Reber et al (1998), Mamikoglu et al (2000Mamikoglu et al ( , 2002, Carlini et al (2002), entre outros.…”
unclassified
“…Com relação às distâncias das três principais constrições identificadas no rinograma (dAST 1 , dAST 2 , dAST 3 ), Camargo (2008) observou, nos adultos analisados por Gomes (2004), valores médios de 2,12, 3,82, 5,74cm, respectivamente. No grupo com obstrução observou-se, do lado direito, médias de 2,14, 4,00 e 5,83cm, respectivamente, e, do lado esquerdo, 2,24, 4,04 e 5,88, respectivamente, ou seja, valores maiores, particularmente para dAST1 e dAST2.…”
Section: Resultsunclassified
“…Em indivíduos com obstrução de vias aéreas nasais de diferentes etiologias, valores subnormais foram observados por autores como Grymer et al (1989), Hilberg et al (1990, Lenders e Pirsig (1990), Lenders et al (1991), Grymer et al (1993), Grymer et al (1995), Fisher et al (1995), Roithmann et al ( , 1997, Mann et al (1997), Shemen e Hamburg (1997), Gilain et al (1997), Kunkel et al (1997), Reber et al (1998), Suzcs (1998), Kemker et al (1999), Urpegui et al (1999), Sung et al (2000), Mamikoglu et al (2000Mamikoglu et al ( , 2002, Pirilä e Tikanto (2001), Voegels et al (2002), Carlini et al (2002), Egeli (2004), Hurst et al (2006), Kjaergaard (2008), Trindade et al (2009). Foram incluídos no estudo pacientes que apresentavam queixa de obstrução nasal confirmada pela identificação de desvio septal e/ou hipertrofia de conchas nasais inferiores ao exame físico.…”
Section: Introdução Introdução Introdução Introdução 1 Introduçãounclassified